COLLISIONS OF ROAD VEHICLES WITH BRIDGE COLUMNS (Advances in Civil and Architectural Engineering, 2021)
As speed limits and traffic on city roads continue to increase, collisions between road vehicles and bridge columns are becoming more common. Current regulations analyze collision with one major simplification: replacing dynamic action with the equivalent static force. In the present paper, we develop a numerical model of a typical Croatian overpass and loaded it with an equivalent static load according to the EN1991-7 and ASSHTO LRFD provisions, analyzing the differences in overpass behavior between them. We compared this to a simplified dynamic analysis, which assumed the impact forces to be impulse loads. Protection measures can be installed around bridge columns that reduce the probability of vehicle collision and open possibilities for reducing collision forces.